Integrasi Asuhan Spiritual: Peran Tenaga Kesehatan dalam Pendampingan Tayamum bagi Pasien Muslim - Rohmawati, Hesti Gea; Rizky, Kharisto Ahadist; Fatkha, Zakiya Ramada; Amiruddin, Muhammad (Maliki Interdisciplinary Journal, 2025)
Health care in Islam emphasizes not only physical healing but also the fulfillment of each patient’s spiritual needs. One form of this integration is the role of health workers (NAKES) in assisting patients to perform tayamum when medical conditions prevent the use of water. This study aims to describe the role and understanding of health workers regarding tayamum as a form of religious concession (rukhsah), as well as to explore how such assistance affects patients’ spiritual tranquility. The approach used is a literature review of various studies and community service reports discussing the practice of spiritual care in hospitals. The findings show that spiritual care training significantly enhances nurses’ ability and sensitivity in accompanying patients during worship. This assistance not only helps maintain the regularity of worship but also fosters calmness, motivation for recovery, and a stronger connection between patients and their religious values. Although several challenges remain, such as limited time, facilities, and understanding of Islamic jurisprudence, solutions like regular training, the provision of tayamum media, and collaboration with religious leaders have proven effective. Overall, the involvement of health workers in tayamum reflects a holistic health care model addressing the body, mind, and soul of patients and contributes to improving their quality of life during treatment.